O Estudo de Impacto de Vizinhança (EIV) no Brasil: desafios e potencialidades de sua aplicação no Município de São Carlos (SP) - Santilli, Caio Arantes (2023)
The National Urban Policy, consolidated by Federal Act 10.257/2001, called City Statute, based on basic principles of the social function of the city and property and on the central objective of a socially fair and environmentally balanced city, still has poorly implemented and studied instruments, even after more than 20 years of its enactment. One of these is the neighbourhood impact study (NIS), considered an instrument of urban environmental planning and democratization of urban management. The NIS still faces many challenges to its implementation by municipalities. Such challenges are more aggravated in a context of neoliberal inflection of public policies, which also ends up weakening the City Statute completely. This research aims to propose subsidies and improvements regarding the implementation of the NIS in the municipality of São Carlos (SP), looking for optimize the role of this instrument within the municipal licensing process. To this end, a Systematic Bibliographic Review (SBR) was carried out, to outline an overview of the scientific literature on NIS in Brazil. The result of the SBR allowed us to point out reference authors, the types of publications and events in which the NIS is the focus of research. A total of 161 references studies on NIS were identified, 54 of which highlight implementation challenges, and 72 that present possibilities for improving the instrument. Subsequently, the regulatory trajectory of NIS was evaluated in São Carlos (SP), using a qualitative analysis of the legal documents regarding the instrument in the municipality. The results showed that legislation has matured in terms of meeting criteria that aim to achieve the principles of NIS, although a specific law has not yet been approved. At last, the role played by the NIS in licensing processes for land subdivision undertakings for housing purposes in São Carlos was analyzed. An analysis was made of 13 administrative processes, out of a total of 33 selected, which resulted in the approval of these projects, whose decree was published between 2006 and 2018. The functions identified in the analyzes were divided into two groups: 1) urban licensing process support tool and 2) democratic management support tool. The first was performed in four analyzed processes, while the second was observed in two. In addition to the role played by the instrument, the main challenges were identified, and related to possible improvement measures. The weak regulation of the instrument was identified as the main challenge, which can be overcome through the elaboration of appropriate specific legislation. Another challenge is the scarcity of conclusive technical reports. This challenge can be overcome with the provision of a Term of Reference, the definition of basic criteria and general guidelines, which will also contribute to clarifying the different conditioning measures applied to the approval of projects. The precarious popular participation found in the analyzed processes can be improved through the regulation of public hearings and wide publicity of documents and processes.